ANALISIS STRUKTUR ATAS JEMBATAN LENGKUNG RANGKA BAJA TIPE PARKER BENTANG 60 M KELAS A MENGGUNAKAN APLIKASI MIDAS CIVIL - Heri Sutanto; Ery Budiman; Muhammad Adrian (Teknologi Sipil : Jurnal Ilmu Pengetahuan dan Teknologi, 2026)
With the development of science and technology of iron and steel smelting and along with the development of the times that demand innovation, various methods and software have been discovered, one of which is the Midas Civil software. This study aims to determine the largest axial force on each element that occurs due to the combination of loads through the Midas Civil software and to determine the nominal tensile/compressive resistance that occurs due to the largest axial force and to determine the profile of the steel frame structure required for the bridge superstructure. In analyzing the Sambera bridge in Tanjung Limau Village, Muara Badak District, Kutai Kartanegara Regency. The results of the steel frame arch bridge planning with a parker type bridge height of 10 meters, width of 9 meters and a bridge length of 60 meters with a compressive axial force of 10079.06 kN and a tensile axial force of 7701.53 kN. The profile of the upper side member, lower side member, and middle side member is IWF 498×432–45/70, the longitudinal girder profile is IWF 356×352–14/22, the transverse girder profile is IWF 458×417–30/50, the wind tie profile is IWF 304×301–11/17 where the planned loading, the results of bridge component calculations, and the analysis planning of Midas Civil software have met the requirements to provide a safe, comfortable and sturdy parker type steel frame arch bridge for its users.